Techno-economic Assessment of Floating Offshore Wind Energy in the Philippines - Alec Venzo Abella; John Michael Pasaraba; Job Immanuel Encarnacion (한국해양공학회지)
Offshore wind development in the Philippines remains at a standstill owing to the relatively high cost of the technology despite the government’s ambitious goal to produce 19–50 GW by 2050. Previous studies have shown that bottom-fixed turbines can be utilized to reach the lower end of the production target. Still, most potential can be achieved in greater depths where floating turbines are more appropriate. Therefore, this study performs a techno-economic assessment for floating offshore wind energy using global information system (GIS) software to analyze the technical and economic potential of floating offshore wind energy in the Philippines. Data from the Global Wind Atlas was used to obtain the technical potential of sites that may be used for floating offshore wind turbines. Exclusion zones are set up according to distance from shore, marine protected areas, oil and petroleum sites, shipping lanes, and submarine cables. Factors on distance to shore, port, and substation, as well as natural hazards and bathymetry, are considered according to a weighted analytic hierarchical process. The net present value (NPV) of each potential site is then calculated by considering the capital, operational, and decommissioning cost of a site at a 6% interest rate and 25 years of operational life. Results show that there is a total potential of 813 GW that can be produced from a total of 20 non-contiguous sites. However, the current feed-in tariff (FIT) rate of 8.53 Php/kW is insufficient to make any sites profitable as all NPVs are negative. The breakeven prices can guide the Philippines government to set an appropriate rate at a minimum of 10.14 Php/kW.